INSTITUTIONAL INVESTORS, LEVERAGE, DAN PROFIBILITAS TERHADAP FLEKSIBILITAS AKUNTANSI PERUSAHAAN - Islahuddin Islahuddin; Akramadina Akramadina (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
Abstract            The purpose of this study is to examine and analyze the influence of institutional investors, leverage, and profitability for firms accounting flexibility. The population of this study is manufacturing companies listed in the Indonesia Stock Exchange between 2009 and 2011. This study is a hypothesis testing research that involve 51 firms.            The data is obtained from audited financial reporting period between 2009 and 2011. This study found that institutional investors, leverage and profitability simultaneously have influence for firm accounting flexibility, institutional investors has positive influence for firm accounting flexibility, leverage has negative influence for firm accounting flexibility and profitability has negative influence for firms accounting flexibility.            Keywords:  Institutional investors, leverage, profitability, and firms accounting flexibility